2021
DOI: 10.1039/d0bm01696a
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of extracellular vesicles from microalgae: towards the production of sustainable and natural nanocarriers of bioactive compounds

Abstract: Biophysical and biochemical characterisation of microalgae-derived extracellular vesicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 55 publications
2
61
0
Order By: Relevance
“…Moreover, the promotion of IL-6 expression may be a mechanism for the pro-angiogenic effect and wound healing (Yin et al, 2019). As the existence of extracellular vesicles was confirmed in other microalgae (Picciotto et al, 2021), it is reasonable to propose similar mechanisms for live Euglena cells for skin wound healing. Additional elaborately designed experiments would provide strong evidence to support this case.…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, the promotion of IL-6 expression may be a mechanism for the pro-angiogenic effect and wound healing (Yin et al, 2019). As the existence of extracellular vesicles was confirmed in other microalgae (Picciotto et al, 2021), it is reasonable to propose similar mechanisms for live Euglena cells for skin wound healing. Additional elaborately designed experiments would provide strong evidence to support this case.…”
Section: Discussionmentioning
confidence: 62%
“…EVs showed many interesting characteristics for potential use as therapeutic molecules and drug delivery systems. Indeed, EVs showed low immunological response, low toxicity, and these vesicles are able to cross various barriers, and showed the ability to transport and protect their cargo [ 89 , 92 ]. EVs have been evaluated for their potential to produce nanomedicine-based therapeutics; thus, the research has been focused on the possibility to use engineered EVs as vectors in specific therapies [ 91 ].…”
Section: Microalgae Engineering For the Production Of Pharmacological Proteinsmentioning
confidence: 99%
“…EVs have been evaluated for their potential to produce nanomedicine-based therapeutics; thus, the research has been focused on the possibility to use engineered EVs as vectors in specific therapies [ 91 ]. EVs from 18 different strains of microalgae have been isolated and characterized [ 92 ]. The EVs were approximately 90–160 nm in size, and microalgae-based EVs protein showed positive reactivity for the target protein of the EVs.…”
Section: Microalgae Engineering For the Production Of Pharmacological Proteinsmentioning
confidence: 99%
“…In such a context, we recently identified microalgae as a novel natural source of EVs, called nanoalgosomes or simply algosomes ( Adamo et al, 2021 ; Picciotto et al, 2021 ). Microalgae are microorganisms (mostly photosynthetic and autotrophic) considered a promising source of natural bioactive macromolecules such as pigments, polyunsaturated fatty acids, vitamins, and polysaccharides ( Cuellar-Bermudez et al, 2015 ; Khan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we evaluated different microalgal species for their capability to produce EVs ( Picciotto et al, 2021 ) and we identified the marine chlorophyte microalga Tetraselmis chuii (T. chuii) as one of the most promising biosource for a large-scale production of EVs ( Adamo et al, 2021 ). Beyond its capability to produce EVs with a high yield, T. chuii has also an interesting content of valuable natural pigments, including lutein and β -carotene ( Picciotto et al, 2021 ), and it has been approved as a novel food for human consumption ( European Commission, 2017 ).…”
Section: Introductionmentioning
confidence: 99%